2016
DOI: 10.5897/ajfs2016.1441
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Blighia sapida (k. Koenig) aril powder level in diet on the growth and the well-being of albino Wistar rats

Abstract: The aim of the present investigation was to evaluate the impact of Blighia sapida aril level in diet on the growth of albino Wistar rats and their welfare. A quantity of B. sapida arils was cooked and lyophilized. Thirty six young albinos Wistar rats teams up in six with six homogeneous groups were used for a four weeks research. Young rats group were fed ad libitum with six different diets which can be distinguished by the level of B. sapida arils powder. There were control diet (0% B. sapida arils powder), d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Previous studies showed that Blighia sapida arils consumption at degree close to 50 % of the daily nutritional intake did not have any impact on the growth of rats which consumed these diets [1]. In fact coat quality, the well-being and the lipids parameters of the rats were normal in comparison to that of rats which consumed a usual control diet call AIN-93G [2].…”
Section: Introductionmentioning
confidence: 84%
“…Previous studies showed that Blighia sapida arils consumption at degree close to 50 % of the daily nutritional intake did not have any impact on the growth of rats which consumed these diets [1]. In fact coat quality, the well-being and the lipids parameters of the rats were normal in comparison to that of rats which consumed a usual control diet call AIN-93G [2].…”
Section: Introductionmentioning
confidence: 84%
“…Crude Fibre Content Ackee aril apples have been identified as a rich source of dietary fibre, which is beneficial for digestion and offers numerous health advantages. These include lowering cholesterol levels and reducing the risk of cardiovascular diseases, obesity, colon diseases, and type 2 diabetes (Anupama and Sunilkumar, 2019;Ouattara et al, 2010).…”
Section: Crude Fat Contentmentioning
confidence: 99%
“…The ackee (Blighia sapida) is a medium-sized tree in the Sapindaceae family native to West Africa. The plant is said to have been introduced from Guinea to the Antilles, and to Jamaica in 1789, thanks to the slave trade [2,5,7,8]. It is a species close to the "lychee" (Litchi chinensis).…”
Section: Botanical Aspects Of Blighia Sapidamentioning
confidence: 99%
“…Proteins are also well represented with 20% while carbohydrates are low, representing less than 10% [14]. Aril is also rich in vitamin C and contains various other vitamins and minerals, mainly magnesium, sodium, calcium and phosphorus [7,8,10,15,16]. However, the aril contains, when the fruit is not ripe, a toxic compound, hypoglycin, which exists in two forms A (Figure 5) and B (Figure 6) [2,8,17].…”
Section: Phytochemical Composition Of Blighia Sapida Arilmentioning
confidence: 99%
See 1 more Smart Citation